Dynamic Task Scheduling Based on Abelian Sandpile and Rotor-Router Models - Nahapetyan, Hayk E.; Poghosyan, Suren S. (Mathematical Problems of Computer Science, 2021)
This study is dedicated to the possible usage of self-organized criticality models in large-scale computing systems for load balancing and energy-awareness. Methods and software tools aimed at modeling and visualization of dynamic tasks scheduling in virtual distributed systems constructed over sandpile and rotor-router models, are also presented